Propagation properties and radiation forces of partially coherent self-shifting cosine-Gaussian beams - Peng, Xi; He, Shangling; He, Yingji; Deng, Dongmei; Zhao, Daomu (Frontiers in Physics, 2022)
In the ABCD optical system, the propagation properties and the radiation forces are obtained by studying the cross spectral density of partially coherent self-shifting cosine-Gaussian beams. A self-shifting phenomenon occurs when the beams propagate in the strongly nonlocal nonlinear medium. The shifting parameters could influence the bend characteristics of the propagation trajectory and the beam center, while the power ratio affects the periods of the parabolic trajectory. Furthermore, the radiation forces on a Rayleigh particle in the focusing optical system are studied, and the obtained force distributions depend on the refractive index, the shifting parameters, and the coherence widths. What we report here has potential applications in optical communication and optical tweezing.